The symptoms of postpartum depression observed by family members: A pilot study - Nguyen, Huong Thi Thanh; Do, Ly Thi Kim; Pham, Huong Thi Thu; Hoang, Anh Phuong; Truong, Hoa Thi; Nguyen, Huyen Thi Hoa (Frontiers in Psychiatry, 2022)
Postpartum Depression (PPD) is a burden on women's mental health after delivery, predominantly occurring in the 1st year. PPD poses a threat to the mother's life and affects the quality of childcare. Early detection by family members of depressive symptoms is critical. This study aimed to examine the role of family members in reporting depressive symptoms of PPD among new mothers. A cross-sectional study was conducted, where 56 family members were asked to report depressive symptoms observed in new mothers. At the same time, the new mothers were also screened for PPD using the Edinburgh Postpartum Depression Scale (EPDS). Binary logistic regression was performed. Depressive symptoms of new mothers reported by family members, including emotional and behavioral disturbance, being under stress, high anxiety, isolation, changing lifestyle, and inability to take care of their children, were found as predictors of PPD.